Dermoscopy of Amyloidosis Cutis Dyschromica - Meghana C. Rane; Sunanda A. Mahajan (Wolters Kluwer Medknow Publications, 2024)
Amyloidosis cutis dyschromica is a very rare form of primary cutaneous amyloidosis characterized by prepubertal onset of hyper and hypopigmented spots and amyloid deposits in the papillary dermis. We report two cases of this condition highlighting its dermoscopic findings.